Analisis Indeks Kepuasan Masyarakat terhadap Program Corporate Social Responsibility Garitan Kalongliud PT ANTAM (Persero) Tbk UBPE Pongkor - Arif Rahman Saleh; Edy Ayuba; Nabilla Dea Lukita; Yudianto Yudianto (Indonesian Journal Publisher, 2026)
Corporate Social Responsibility (CSR) programs in the mining sector play a strategic role in strengthening community resilience and supporting sustainable livelihoods, particularly in preparation for post-mining conditions. This study aims to analyze community satisfaction with the Garitan Kalongliud CSR Program implemented by PT ANTAM (Persero) Tbk UBPE Pongkor using the Community Satisfaction Index (CSI) as an evaluation framework. An evaluative mixed-methods approach was employed by integrating quantitative and qualitative data. Quantitative data were collected through a survey of 25 respondents selected purposively from 214 program beneficiaries, while qualitative data were obtained through in-depth interviews, field observations, and document analysis. The quantitative data were analyzed using CSI calculations, whereas qualitative findings were used to enrich the interpretation of community perceptions and program outcomes. The results indicate that the Garitan Kalongliud Program achieved a CSI score of 3.63, equivalent to a converted score of 90.82, placing it in the “Very Good” category. High community satisfaction was associated with the program’s relevance to local needs, active community participation, effective facilitation, and its positive economic, social, and environmental impacts. Beneficiaries also demonstrated strong readiness to continue program activities independently, indicating substantial sustainability potential beyond the mining period. These findings suggest that the Community Satisfaction Index is an effective instrument for evaluating CSR performance and can serve as a strategic basis for improving community empowerment, strengthening social license to operate, and supporting sustainable post-mining development.